Association of hearing loss and risk of depression: a systematic review and meta-analysis - Wei, Jingxuan; Li, Yang; Gui, Xiongbin (Frontiers in Neurology, 2024)
Background Previous studies have suggested a possible link between hearing loss and the risk of depression. However, the strength of this association remains uncertain across varying follow-up periods, age groups, cohort studies, and longitudinal study designs. Methods We conducted an extensive literature search across PubMed, Embase, and the Cochrane Library databases to retrieve pertinent studies. The quality of observational studies was assessed using the Newcastle–Ottawa Scale. Synthesis and meta-analysis of odds ratios (ORs) along with corresponding 95% confidence intervals (CIs) were performed using Stata 14.0. Funnel plot analysis and Egger’s regression test were utilized to assess potential publication bias. Results This meta-analysis comprised 24 cohort studies conducted between 2007 and 2024, with sample sizes ranging from 548 to 254,466 participants. Among these participants, 24,304 had experienced depression events. The pooling analysis shows that hearing loss is associated with an increased risk of depression (OR = 1.35; 95%CI: 1.27–1.44). In the subgroup analysis, the retrospective cohort exhibited a slightly higher risk of depression compared to the prospective cohort (OR = 1.43; 95% CI: 1.30–1.58). There are differences in the risk of depression among young, middle-aged, and older individuals, with older adults facing a higher risk (OR = 1.33, 95% CI: 1.21–1.45). Additionally, the risk of depression was slightly higher in the sudden sensorineural hearing loss (SSNHL) group compared to the non-SSNHL group (OR = 1.62; 95% CI: 1.27–2.07). Furthermore, in cohorts with a follow-up time ≥ 5 years, the risk of depression was higher compared to those with <5 years of follow-up (OR = 1.39; 95% CI: 1.26–1.54). Conclusion Our meta-analysis shows that hearing loss increases the risk of depression. These findings provide evidence that hearing loss should be recognized as an independent risk factor for depression. Clinical trial registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42024502043.